(untitled) (Research, Society and Development, 2025)
Paradental inflammatory cyst (PIC) is an odontogenic cyst associated with episodes of mechanical trauma and is found near the lateral cervical margin of the dental root of a partially erupted tooth. It is typically located distal to mandibular third molars and rarely appears in the maxilla. This study aims to report a rare case of a PIC in the maxilla associated with the impaction of tooth 15 and with a 6 month post operative follow-up. A 20-year-old female patient with no systemic alterations was referred by an orthodontist due to the absence of tooth 15. Clinical examination revealed no significant alterations in the soft and hard tissues or the missing tooth. Radiographic examination identified a supernumerary tooth between teeth 16 and 15, as well as a hypodense lesion between teeth 14 and 16 in their root region. Differential diagnoses included dentigerous cyst, traumatic bone cyst, and chronic inflammatory lesion. The proposed treatment involved surgical removal under local anesthesia, including osteotomy for lesion access, extraction of the supernumerary tooth, extensive curettage, and complete enucleation of the intraosseous lesion. Histopathological examination revealed a cystic capsule lined by stratified squamous epithelium, with dense connective tissue and moderate lymphoplasmacytic inflammatory infiltrate, along with areas of diffuse hemorrhage, confirming the definitive diagnosis of PIC. The postoperative period was uneventful, and the patient was followed up for 30 days without signs of recurrence, being cleared for orthodontic treatment. In conclusion, PIC is an uncommon lesion that rarely occurs in the maxilla, which accurate diagnosis requires a thorough correlation of clinical, radiographic, and histological data, with a low recurrence rate.